Modernisasi Pondok Pesantren Salafi : Kepemimpinan dan Pembelajaran Transformasi dalam Pendidikan Agama Islam - Ali Nurdin; Samudi Samudi (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
The aim of this research is to examine, analyze and describe the modernization of Salafi Islamic boarding schools with regard to leadership and Islamic religious education learning. This research method uses a qualitative method with a phenomenological paradigm type, the unit of analysis is the Salafi Islamic Boarding School al-Hidayah Pandeglang Banten. The data collection is: observation, in-depth interviews and documentation. Theory validation uses triangulation of data sources. The findings in this research are that the modernization of Salafi Islamic boarding schools is influenced by awareness factors from the organizers and guidance from the government, but is still hampered by cultural resistance from each Salafi Islamic boarding school, however the modernization process continues and has occurred in educational leadership and learning Islam. The forms of modernization at Salafi Islamic boarding schools are related to leadership, namely the placement of leaders through a Decree from the Chairman of the Foundation that oversees the Islamic boarding school, their appointment is based on criteria and qualifications of Islamic religious scientific ability, Islamic boarding school education and the ability to guide, care for and teach the students. Meanwhile, learning models include: classical, structured and tiered learning strategies, using sorogan, bandungan, bahtsul masa'il, tasyrifan, muhadarah, pasar, muhafazhah, practice of worship and reading the Koran, conventional and modern IT-based learning media. as well as carrying out written, oral and internship learning tests for students in a programmed and ongoing manner.